2020
DOI: 10.1101/2020.09.11.20192591
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Saliva as a potential clinical specimen for diagnosis of SARS-CoV-2

Abstract: Background It is almost nine months, still there is no sign to stop the spreading of the COVID-19 pandemic. Rapid and early detection of the virus is the master key to cease the rapid spread and break the human transmission chain. There are very few studies in search of an alternate and convenient diagnostic tool which can substitute nasopharyngeal swab (NPS) specimen for detection of SARS-CoV-2. We aimed to analyse the comparison and agreement between the feasibility of using the saliva in comparison to NPS f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…We also assessed if patient symptomatology could explain variable diagnostic performance between saliva and NP sampling. We found that only a few studies provided a direct comparison between asymptomatic ( 16 , 19 , 33 ) and symptomatic patient data ( 17 , 18 , 21 23 , 25 , 27 , 28 , 34 , 35 , 37 , 39 , 40 ) that could be parsed and extracted for analysis. We found that % positive saliva was similar between asymptomatic and symptomatic patients (87% [95% CI 70 to 98%] versus 88% [95% CI 79 to 95%], respectively).…”
Section: Resultsmentioning
confidence: 99%
“…We also assessed if patient symptomatology could explain variable diagnostic performance between saliva and NP sampling. We found that only a few studies provided a direct comparison between asymptomatic ( 16 , 19 , 33 ) and symptomatic patient data ( 17 , 18 , 21 23 , 25 , 27 , 28 , 34 , 35 , 37 , 39 , 40 ) that could be parsed and extracted for analysis. We found that % positive saliva was similar between asymptomatic and symptomatic patients (87% [95% CI 70 to 98%] versus 88% [95% CI 79 to 95%], respectively).…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of our selection criteria, 127 of those studies were excluded and 23 studies 21 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 met our inclusion criteria ( table ). Of these, 14 studies were from the USA, 21 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 four were from European countries, 60 , 61 , 62 , 63 two were from Eastern Mediterranean countries, 64 , 65 and the rest were from Canada, 66 India, 67 and China. 68 7973 individuals with suspected SARS-CoV-2 infection, who were mostly symptomatic outpatients presenting to dedicated testing sites or emergency departments, were included from the 23 eligible studies.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies (16 cohorts) were included. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] A total number of patients for sensitivity and specificity comparison was 5863 (median:158; interquartile range: 94-234) (Table S1). Mean or median age of patients ranged from 33.5 to 44.9 years in six studies (seven cohorts) where information was available, and three studies included some pediatric patients.…”
Section: E T T E R T O T H E E D I T O R Saliva-based Testing For Diagnosis Of Sars-cov-2 Infection: a Meta-analysismentioning
confidence: 99%